2015
DOI: 10.1139/apnm-2014-0465
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect measurement of neuromuscular fatigue in Canadian football players

Abstract: This study assessed the effects of a fatiguing game simulation (G-Sim) on the balance of collegiate Canadian football players. The purpose of the study was to evaluate postural control as a potential tool for monitoring neuromuscular fatigue (NMF) in collision-based team sports. Fifteen male Canadian football players were recruited (mean±SD: age 21.8±1.6 years, weight 97.6±14.7 kg). Indirect NMF measures (postural sway and countermovement jump (CMJ)) were performed 24 h before (TBase), immediately before (TPre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Knee-extensor MVC, decrements in which are considered as a global measure of fatigue involving peripheral and central components, was reduced by 11% after 45 min of the simulated match. After 90 min, the ability to generate maximal force was further reduced, and this reduction in strength was similar to the results of simulated and actual intermittent exercise performance (~15%; Clarke et al 2015;Robineau et al 2012), but larger than others (Andersson et al 2008;Ascensao et al 2008;Ispirlidis et al 2008;Rampinini et al 2011;Thorlund et al 2009). Extra time elicited further reductions in MVC compared to FT (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Knee-extensor MVC, decrements in which are considered as a global measure of fatigue involving peripheral and central components, was reduced by 11% after 45 min of the simulated match. After 90 min, the ability to generate maximal force was further reduced, and this reduction in strength was similar to the results of simulated and actual intermittent exercise performance (~15%; Clarke et al 2015;Robineau et al 2012), but larger than others (Andersson et al 2008;Ascensao et al 2008;Ispirlidis et al 2008;Rampinini et al 2011;Thorlund et al 2009). Extra time elicited further reductions in MVC compared to FT (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Participation in soccer results in high levels of metabolic (Rampinini et al 2011), mechanical (Akenhead et al 2013), and perceptual stress (Impellizzeri et al 2004). The aetiology of soccer-specific fatigue, which manifests transiently during simulated and actual match-play, has been hypothesised to be due to several putative mechanisms including, compromised excitation-contraction coupling (Clarke et al 2015;Rampinini et al 2011), depletion of endogenous fuel sources (Bendiksen et al 2012), ionic disturbances (Bangsbo et al 2006), and dehydration (Laitano et al 2014). Despite these investigations, the precise mechanisms of fatigue are yet to be delineated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests have shown that players perform 7-10% worse in a counter movement jump after a football match or similar fatiguing activity. After 24 to 72 hours of recovery following the fatiguing activity, performance has returned to baseline values [61][62][63]. Similar results have been shown using sprint tests with an immediate 2-10% decline in performance after a match.…”
Section: Fatiguesupporting
confidence: 80%
“…One possible explanation for these associations between match congestion and injury rates could be that players suffer from residual fatigue after a match if they have not been given enough time to recover between two match exposures. However, most previously published studies have shown that signs of muscular fatigue often disappear within 72 hours after a football match, [61][62][63][64][65][66][67] whereas the results of Paper III suggest an increased injury rate up to 5 days after a previous match. Other studies have shown that the biomechanical properties of muscles change as they are fatigued after a football match or similar activity, lowering the production of maximal force and altering the angle of peak torque [125][126][127].…”
Section: Short-term Match Congestionmentioning
confidence: 86%